Enhancing Elementary Literacy Skills through a Contextualized Coastal Course Book: A Developmental Study in Bengkulu, Indonesia - Susanta, Agus; Dewi Rahimah; Irwan Koto; Edi Susanto; Muchlis, Effie Efrida; Mela Azizah (Universitas Muhammadiyah Surakarta, 2023)
Teaching materials designed using local contexts are important in improving students' literacy skills. The lack of teaching materials to support these skills causes low student literacy achievements in elementary schools. This study aims to design a course book, grounded in the coastal context of Bengkulu, to enhance the literacy skills of elementary school students. The research employs a developmental approach using the ADDIE model, which encompasses five stages: (1) analysis, (2) design, (3) development, (4) implementation, and (5) evaluation. The subjects of the study are fifth-grade students from elementary schools in Bengkulu City. The study is conducted in three phases: expert trials, limited trials, and wide-scale trials. Data is collected through both tests and non-tests. The instruments used for data collection include product validity sheets, practicality questionnaires, and literacy test instruments. Descriptive statistical analysis is utilized for data analysis. The result of the research suggests that the course book, based on the Bengkulu coastal context, meets the criteria for validity, and practicality, and effectively enhances the literacy skills of elementary school students. Teaching materials that integrate with coastal contexts have been proven to support students' thinking skills, one of which is mathematical literacy.